Peranan Koperasi Dalam Pengembangan Sistem Agribisnis Kakao (Studi Kasus: Koperasi Perkebunan Kakao Bireuen) - Jamil, Muhammad; Budi, Setia (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2022)
There is still great potential for the development of cocoa plants in Kabupaten Bireuen is a great opportunity to improve cocoa agribusiness in a sustainable, one of them is through institutional roles. However, the Kabupaten Bireuen government still has several problems in running the cocoa agribusiness system starting from the upstream subsystem to support services. Problems in the upstream subsystem and farming, namely farmers have not been able to fully implement the frequent harvest system, pruning, sanitizing and fertilizing (PsPSP) as well as fermentation. Even though the Bireuen Cocoa Plantation Cooperative has provided trainings related to the PsPSP system and the fermentation. This study aims to determine the cocoa agribusiness system in Kabupaten Bireuen and to find out the role of the Cocoa Plantation Cooperative that has been carried out so far. The sample criteria in this study were 34 cocoa farmers who were active members of the Bireuen Cocoa Plantation Cooperative. Data analysis in this study used a qualitative descriptive method with data measurement using a Likert scale.  The  results  showed  that  the  cocoa  agribusiness  system  in  Kabupaten Bireuennot well integrated, while in general the role of cooperatives in the development  of  the  cocoa  agribusiness  system  is  large  with  an  index  value  of 69.92%.The role of cooperatives in aid distribution activities is categorized as large with an index value of 73.94%,training activities have a big role with the category 79.65%, mentoring activities have a big role with an index value of 67.12% and the collection of results has a small role with an index value of 58.97%.